Rancang Bangun Alat Uji Kekuatan Material Polimer dan Komposit Polimer Berpenguat Serat Alam - Manalu, Ferry Rippun G; Basuki, Widodo Widjaja (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2025)
Current engineering technology places great emphasis on efficient and energy-saving construction. Nowadays, research and development of engineering materials are more directed at relatively strong, stable and lightweight materials. Polymers and natural fiber reinforced polymer composites are one of those that can meet these needs and are being researched. To achieve optimal results, the research must be supported by appropriate test equipment that can properly characterize the materials being developed. This research aims to design a mechanical and electrical tensile testing device especially for polymers and polymer composites. The research produced a prototype of a tensile testing device that has a maximum load capacity of 20.25 kN. The success of this research is proven by the strength of PMMA, which was tested using this device. The test results showed that PMMA has a tensile strength of about 58.2 and 60.7 MPa. This value is within the range of PMMA strength obtained from the literature.